2008
DOI: 10.1007/s00467-008-0749-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal expression of alpha-smooth muscle actin and c-Met in children with Henoch–Schönlein purpura nephritis

Abstract: Alpha-smooth muscle actin (alpha-SMA) is the actin isoform that predominates within vascular smooth-muscle cells and plays an important role in fibrogenesis. On the other hand, c-Met is the receptor for hepatocyte growth factor (HGF), which plays a role in protection from injury and has anti-fibrogenetic effects. To clarify whether alpha-SMA and HGF are associated with the progression of renal injury in Henoch-Schönlein purpura nephritis (HSPN), we evaluated the renal expression of alpha-SMA and c-Met in HSPN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
3
27
0
1
Order By: Relevance
“…As to the other prognostic factors, Kawasaki et al reported that the expression of renal alpha -SMA was a predictor of poor prognosis in HSPN patients 34) . Alpha -smooth muscle actin (alpha -SMA) is the predominant actin isoform within vascular smoothmuscle cells and plays an important role in fibrogenesis.…”
Section: Course and Clinicopathological Correlationsmentioning
confidence: 99%
“…As to the other prognostic factors, Kawasaki et al reported that the expression of renal alpha -SMA was a predictor of poor prognosis in HSPN patients 34) . Alpha -smooth muscle actin (alpha -SMA) is the predominant actin isoform within vascular smoothmuscle cells and plays an important role in fibrogenesis.…”
Section: Course and Clinicopathological Correlationsmentioning
confidence: 99%
“…Alpha-SMA is an actin isoform and is commonly used as a marker for myoepithelial cells (Schon et al 1999;Nagamoto et al 2000;Kawasaki et al 2008). Diverse keratins and alpha-SMA have been established as markers of differentiation, and their expression pattern varies with the type of epithelium, stage of development, and degree of differentiation (Moll et al 1982b(Moll et al , 2008Moll and Moll 1992;Schon et al 1999;Saga 2002;Lu et al 2012;Lu and Fuchs 2014;Li et al 2015b).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, the renal expression of alpha-smooth muscle actin (a-SMA) and c-Met, which is the receptor for hepatocyte growth factor, has also been associated with the progression of renal injury in patients with HSPN [34]. Kawasaki et al studied 35 patients in Japan with biopsyproven HSPN who were categorized into three groups: (1) nephritis with an ISKDC histological grade (the classification system used by the International Study of Kidney Disease in Children) of II or less, (2) those with ISKDC grade III or greater and a good prognosis, and (3) those with ISKDC grade III or greater and a poor prognosis.…”
Section: Structure Of Igamentioning
confidence: 99%